2006
DOI: 10.1017/s031716710000473x
|View full text |Cite
|
Sign up to set email alerts
|

Pain Free Efficacy of Sumatriptan in the Early Treatment of Migraine

Abstract: Migraine is a common neurological disorder that is characterized by episodic headaches associated with symptoms such as nausea, visual disturbances, photophobia, and phonophobia. In Canada, approximately 7% of adult males and 22% of adult females suffer from migraine. 1 Migraine symptoms result in a considerable burden with regard to health care utilization, health care costs, and work/productivity loss due to disability and decreased functional status. [2][3][4][5][6] Clinical trials have demonstrated that su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…To our knowledge, our study provides the first evidence that ATP can lower the activation threshold of trigeminal neurons to K+ ions and, hence, can function to promote peripheral sensitization of nociceptive afferent fibers that provide innervation of the meningeal blood vessels and are involved in the pain of migraine. Based on our findings, we propose that DHE, as has been reported for the triptans, may be most beneficial therapeutically if taken early in a migraine attack during the initial stages characterized by peripheral sensitization and when headache pain is mild 57‐59 . In addition, our results provide evidence that DHE should be most effective in treating migraine with aura as these types of attacks are characterized by CSD, an event that triggers increased release of ATP and K+ ions that can lead to activation of trigeminal nociceptive neurons.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…To our knowledge, our study provides the first evidence that ATP can lower the activation threshold of trigeminal neurons to K+ ions and, hence, can function to promote peripheral sensitization of nociceptive afferent fibers that provide innervation of the meningeal blood vessels and are involved in the pain of migraine. Based on our findings, we propose that DHE, as has been reported for the triptans, may be most beneficial therapeutically if taken early in a migraine attack during the initial stages characterized by peripheral sensitization and when headache pain is mild 57‐59 . In addition, our results provide evidence that DHE should be most effective in treating migraine with aura as these types of attacks are characterized by CSD, an event that triggers increased release of ATP and K+ ions that can lead to activation of trigeminal nociceptive neurons.…”
Section: Discussionsupporting
confidence: 76%
“…Based on our findings, we propose that DHE, as has been reported for the triptans, may be most beneficial therapeutically if taken early in a migraine attack during the initial stages characterized by peripheral sensitization and when headache pain is mild. [57][58][59] In addition, our results provide evidence that DHE should be most effective in treating migraine with aura as these types of attacks are characterized by CSD, an event that triggers increased release of ATP and K+ ions that can lead to activation of trigeminal nociceptive neurons. It will be of interest to determine in clinical trials whether more rapid dosing of DHE, as reported for LEVADEX™, will be more beneficial in treating migraine with aura than migraine without aura and whether it will be more effective than triptans.…”
Section: Discussionmentioning
confidence: 83%
“…Several of the acute trials investigate the relationship between the timing of drug intake (in relation to the onset of migraine pain or cutaneous allodynia) and drug efficacy [23, 62, 73, 86, 102, 103, 122, 130]. The results of these trials suggest that “early” triptan administration, while the headache is mild, is more efficient in terms of pain-free outcomes and reduced risk of recurrence when compared to “late” administration, when the headache is moderate to severe.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with very frequent attacks also need to be careful about rapid self-treatment with acute medication so that the maximum monthly dosage is not exceeded. The advantages of early treatment include greater and more rapid efficacy (9,11,13,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). In addition, cutaneous allodynia may develop over the course of the attack, reducing the efficacy of triptans.…”
Section: What's Newmentioning
confidence: 99%
“…Recent randomised, double-blinded, placebo-controlled clinical trials have examined the early use of triptans for therapy of migraine headaches (13,25,26,29,32,(40)(41)(42)(43). In addition, a number of open-label or unblinded studies have been published that show the benefits of treatment during the early phases of a migraine attack (9,11,19,20,22,28,32). The 'Act when Mild' study, performed under carefully controlled conditions with a rigorous study design, showed that improved efficacy could be achieved when attacks were treated within the first hour of an attack or when pain intensity was mild (13).…”
mentioning
confidence: 99%